Biological Applications of Ionic Liquids-Based Surfactants: A Review of the Current Scenario - Sivapragasam, M. (Springer Science and Business Media B.V., 2020)
The paramount features of Ionic Liquids-Based Surfactant, (ILBS) stems from their remarkable properties such as low critical micelle concentration (CMC), high solubilization ability, and better wetting and foaming properties compared to commercially available surfactants. Currently, the types of ILBS synthesized includes those of imidazolium, pyrrolidinium, pyridinium, piperidinium, and amino acid based. The combination of surfactants and ionic liquids (ILs) are particularly relevant to applications such as heterogeneous catalysis and emulsion technologies that rely on the control over their interfacial properties. The ability of ILBS to depict features of ionic liquids (ILs) while aggregating in dilute aqueous solution, and the possibility of switching between these two states protrude applications led to its plentiful applications in the biological scope. This chapter provides a current overview on the biological applications of ILBS which included those of the drug delivery, biomolecule extraction, biocompound separation, enzyme catalysis, and others. Â© Springer Nature Switzerland AG 2020.